(untitled) (Comprehensive Journal of Science, 2026)
In September 2023, the city of Derna witnessed devastating floods caused by Storm Daniel, which resulted in severe human and material losses that unprecedentedly affected the social, institutional, and educational infrastructure. This proposed research aims to examine the attitudes of faculty members at Derna University in order to survey the views of experts (a study sample of 30 faculty members) regarding the role of social media networks in reconstruction efforts after Storm Daniel, particularly in terms of their contribution to disseminating information, exchanging support, and enhancing transparency and community accountability. The study will rely on a mixed-methods approach that combines quantitative questionnaires and qualitative interviews with a sample of faculty members from various colleges at the universities in the municipalities of Derna and Al-Qubbah. The aim is to analyze the relationship between patterns of social media use and the level of trust and satisfaction toward institutional and community reconstruction processes. It is expected that the findings will contribute to the development of effective digital communication strategies that support academic and community participation in reconstruction, and enhance the role of higher education in building community trust and achieving sustainable development in Libya, in alignment with the objectives of the Libya Development and Reconstruction Fund.